POTRET KEHIDUPAN SOSIAL EKONOMI PEDAGANG PAKAIAN DI PASAR WISATA PURWODADI KOTA PEKANBARU - ", Bedi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In this study the authors use survey research base with the type of descriptiveresearch. Sampling technique is done by simple random sampling. Primary dataobtained by observation and using questionnaires. The data analysis usingquantitative methods and frequency tables. Population and sample in this study wasthe Merchants Clothes that are in the city of Pekanbaru Tourism Purwodadi Mart.This study aims to determine the socio-economic life of street traders in the city ofPekanbaru particularly clothing merchants and factors that encourage traders clothingto immigrate to the city of Pekanbaru and why they chose that street merchants into ajob. The usefulness of this research into a particular entries Pekanbaru citygovernment in matters of employment and efforts to restrain the rate of growth,especially migrants from outside the city of Pekanbaru, and this research is alsoexpected to be a reference and comparison to other studies related to this research.Research results generally show that the clothing merchants dominated by ethnicMinangkabau of West Sumatra. This clothing merchants do not need high educationand skills. From most of the clothing traders who perform the migration, thepermanent migrants (settled) on appeal circular migrants (not settle). The level ofincome they earn an average of 100.000 - 200.000 day. Income they earn almostmeet their daily needs. Factors that drive to move and work as street vendors(Clothier) in the city of Pekanbaru is based by 2 main things that is the driving factorof the area of origin and pull factors of the city.Kata Kunci: Clothier, Sosio Economic Life, Tourism Mart